2018
DOI: 10.3390/toxins10060241
|View full text |Cite
|
Sign up to set email alerts
|

Toxins of Locus of Enterocyte Effacement-Negative Shiga Toxin-Producing Escherichia coli

Abstract: Studies on Shiga toxin-producing Escherichia coli (STEC) typically examine and classify the virulence gene profiles based on genomic analyses. Among the screened strains, a subgroup of STEC which lacks the locus of enterocyte effacement (LEE) has frequently been identified. This raises the question about the level of pathogenicity of such strains. This review focuses on the advantages and disadvantages of the standard screening procedures in virulence profiling and summarizes the current knowledge concerning t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 169 publications
(247 reference statements)
0
13
1
Order By: Relevance
“…This low prevalence of eae -positive isolates among non-O157 from ruminants is in accordance to that found 10 years before [ 12 ] and with several other studies [ 36 , 42 , 43 ], but much lower than the 64.3% recently reported in beef cattle in Spain [ 40 ]. Although this might suggest that only a small proportion of STEC shedding herds pose a high risk, results from human clinical cases reported here and elsewhere [ 44 ] showed that isolates also lacking the eae gene can cause gastrointestinal disease. The fact that a significantly higher proportion of non-O157 human isolates were eae -negative than eae -positive, particularly in adults and the elderly, might indicate that these patients were more frequently infected with serotypes other than the top five non-O157 STEC [ 45 ].…”
Section: Discussioncontrasting
confidence: 53%
“…This low prevalence of eae -positive isolates among non-O157 from ruminants is in accordance to that found 10 years before [ 12 ] and with several other studies [ 36 , 42 , 43 ], but much lower than the 64.3% recently reported in beef cattle in Spain [ 40 ]. Although this might suggest that only a small proportion of STEC shedding herds pose a high risk, results from human clinical cases reported here and elsewhere [ 44 ] showed that isolates also lacking the eae gene can cause gastrointestinal disease. The fact that a significantly higher proportion of non-O157 human isolates were eae -negative than eae -positive, particularly in adults and the elderly, might indicate that these patients were more frequently infected with serotypes other than the top five non-O157 STEC [ 45 ].…”
Section: Discussioncontrasting
confidence: 53%
“…Regulation of transcription of virulence factors is of major importance for pathogens, since maximum transcription of such factors at the site of infection may be advantageous for the colonization and infection process. In recent years, STEC strains have been analyzed frequently for the presence and absence of genes encoding virulence factors, such as Shiga toxins, type III effectors, adhesins, and EHEC-hemolysin, or for the qualitative description of their expression (14,(27)(28)(29)(30). In some cases, data on the regulation of virulence factors have been published.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the major virulence genes, various genes suspected to be related to virulence were identified in STEC and EPEC (Dobrindt 2005;Krause et al 2018). The distribution of these STEC/EPEC virulence genes in our commensal strain set was analyzed.…”
Section: Distribution Of Other Stec/epec Virulence Genes In Bovine Anmentioning
confidence: 99%
“…Each STEC lineage appears to have independently acquired phages and plasmids that carry a similar virulence gene set, including the LEE, non-LEE effectors, and plasmid-encoding virulence factors (Ogura et al 2009). LEE-negative STEC strains have occasionally caused HC and HUS, but such strains often carry a virulence determinant alternative to the LEE (Krause et al 2018).…”
mentioning
confidence: 99%